Testing isokinetic muscular fatigue of shoulder internal and external rotation in elite junior tennis players - Ellenbecker, T. S.; Roetert, E. P. (Journal of Orthopaedic & Sports Physical Therapy, 1999)
Abstract: Study Design: Single group, post-test only descriptive analysis of isokinetically measured shoulder internal and external rotation muscular fatigue. Objectives: To determine whether differences in isokinetically measured muscular fatigue exist between shoulder external (ER) and internal rotation (IR) and between the dominant (DOM) and nondominant (NDOM) extremity in elite junior tennis players. Background: The importance of the rotator cuff in stabilizing the humeral head during repetitive athletic overhead motions has been identified in biomechanical investigations. The application of exercise to improve muscular function of the shoulder and prevent injury is a common practice in physical therapy, but shoulder fatigue in tennis players has received little attention in the literature. Methods and Measures: Seventy-two elite junior tennis players (ages 12 to 18) underwent bilateral isokinetic testing with 90° of glenohumeral joint abduction. A muscular fatigue protocol consisting of 20 maximal-effort concentric contractions of ER and IR was used to measure muscular fatigue at 300°/s. A relative fatigue ratio was calculated by dividing the work in the last 10 repetitions by the work in the first 10 repetitions. Higher fatigue ratios indicate improved muscular fatigue resistance. A 2 × 2 ANOVA was used to assess differences in fatigue in DOM versus NDOM arm, and in IR versus ER. Results: Relative muscular fatigue ratios for ER and IR were 69.1 ± 15.3% and 82.93 ± 14.81% for the DOM extremity, respectively. In the NDOM extremity, ER and IR fatigue ratios were 71.13 ± 15.07% and 83.9 ± 16.5%, respectively. These results indicate significant differences between the fatigue ratios for ER and IR. No significant difference between extremities in either ER or IR relative fatigue ratios was found. Conclusions: These data have implications for rehabilitation and conditioning of the rotator cuff musculature.